FAKTOR PREDIKTOR FINANCIAL DISTRESS PERUSAHAAN SUBSEKTOR PARIWISATA, RESTORAN, DAN PERHOTELAN DI BEI (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2022)
The outbreak of Covid-19 in Indonesia weakened the economy of Indonesia, especially for companies in the tourism, restaurant, and hotel sub-sectors. To keep this virus from becoming more epidemic, the government has officially imposed PPKM in all parts of Indonesia which has an impact on many hotels, restaurants, and tourist attractions temporarily closing their businesses for quite a long time. From the temporary closure, it is possible for the company to face financial distress conditions. Financial distress is identical to the condition of declining financial performance before being in a state of bankruptcy which is marked by the inability of a company to fulfill its financial obligations. To be able to avoid bankruptcy in the company, one of these can be done by analyzing financial ratios as an early detection signal of the possibility of financial distress. This study aims to determine the relationship between the independent variables, which include profitability ratios, leverage ratios, and liquidity ratios to the possibility of companies being in a financial distress phase as the dependent variable on 25 tourism, restaurant, and hospitality sub-sector companies listed on the IDX in 2019 and 2020. So that the results of this research can help companies make decisions so they can avoid bankruptcy in the midst of the Covid-19 Pandemic in Indonesia. The result using logistic regression states that profitability ratios, leverage ratios, and liquidity ratios simultaneously have a relationship with financial distress conditions. Partially, profitability ratios and liquidity ratios have a negative effect on financial distress conditions. While the leverage ratio proved to not affect the occurrence of financial distress conditions.